2000
DOI: 10.1590/s1415-47572000000100041
|View full text |Cite
|
Sign up to set email alerts
|

Variability in micronucleus induction with different mutagens applied to several species of fish

Abstract: Fish are often used for screening genotoxicity of water. For such programs, a knowledge of the sensitivity to clastogens, spontaneous micronucleus frequency and cell cycle kinetics of the target tissue is necessary. To investigate the pattern of inter-specific sensitivity to micronucleus induction three species of fish, Tilapia rendalli, Oreochromis niloticus and Cyprinus carpio, were exposed to the clastogens bleomycin (BLM), cyclophosphamide (CP), 5-fluorouracil (5-FU), and mitomycin C (MMC). The binucleate/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 12 publications
3
42
2
4
Order By: Relevance
“…Therefore, it is suggested that micronuclei tests in fish erythrocytes be carried out at various times following treatments, thus making it possible to follow-up the changing micronuclei frequencies. Studies of the micronuclei rates of various fish species showed that they generally peaked between the first and fifth days after treatment (Al-Sabti and Metcalfe, 1995;Grisolia and Cordeiro, 2000). We also conclude from this study that the sampling of peripheral blood is appropriate and sufficient for biomonitoring projects, as it allows to collect several samples from the same individual, without having to sacrifice it.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it is suggested that micronuclei tests in fish erythrocytes be carried out at various times following treatments, thus making it possible to follow-up the changing micronuclei frequencies. Studies of the micronuclei rates of various fish species showed that they generally peaked between the first and fifth days after treatment (Al-Sabti and Metcalfe, 1995;Grisolia and Cordeiro, 2000). We also conclude from this study that the sampling of peripheral blood is appropriate and sufficient for biomonitoring projects, as it allows to collect several samples from the same individual, without having to sacrifice it.…”
Section: Discussionsupporting
confidence: 52%
“…Plusieurs études menées sur les eaux usées provenant des décharges industrielles ou urbaines ont démontré l'existence des activités génotoxiques (Grover et Kaur, 1999 ;Lah et al, 2004 ;Abdel-Migid et al, 2007 ;Junior et al, 2007). L'intérêt sans cesse croissant qu'on porte à la génotoxicité causée par les polluants environnementaux est dû au fait qu'il entraine le développement de différents tests biologiques utilisés pour la détection et l'identification des génotoxiquants dans l'air, l'eau et dans le sol (Grisolia et Cordeiro, 2000). Les tests de génotoxicité sont généralement utilisés pour évaluer le potentiel génotoxique dans l'environnement et au niveau des échantillons d'effluents industriels (Cotelle et al, 1999 ;Grover et Kaur, 1999 ;AbdelMigid et al, 2007).…”
Section: Résuméunclassified
“…The selection of fishes as a model in the ecogenotoxicological studies could be made since fish is a very sensitive bio-indicator of water quality and can highlight the potential danger of new chemicals introduced in the aquatic environment (Bailey et al, 1992) and also respond to toxicants in a manner similar to higher vertebrates (Al-Sabti and Metcalfe, 1995). They have greater ability to metabolize xenobiotics and accumulate pollutants (Grisolia and Corderio, 2000). They are capable of inhabiting practically all zones of the aquatic habitat and have great commercial and recreational value (Solbe, 1993).…”
Section: Fish As a Model For Aquatic Genotoxicologymentioning
confidence: 99%